The roots of the equation
6 x 3 − 3 x 2 + 2 x − 1 = 0 ,
are α , β and γ . Find the value of
1 + α + β + γ + α β + β γ + γ α + α β γ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Creative. But I think it's faster just to add up all the Vieta's equations and get 2.
Log in to reply
Yea, that's what I did at first. I found this solution in hindsight.
Same method!
6 x 3 − 3 x 2 + 2 x − 1 = 0 ⟹ x 3 − 2 1 x 2 + 3 1 x − 6 1 = 0
( x − α ) ( x − β ) ( x − γ ) = x 3 − ( α + β + γ ) x 2 + ( α β + β γ + α γ ) x − ( α β γ )
1 + α + β + γ + α β + β γ + α γ + α β γ = 1 + 2 1 + 3 1 + 6 1 = 2
1 + ( Sum of roots) + (Sum of roots two at a time) + (Products of roots).......
And we get the results......... 1 + (1/2) + (1/3) + (1/6)
6
x
3
−
3
x
2
+
2
x
−
1
=
3
x
2
(
2
x
−
1
)
+
(
2
x
−
1
)
=
(
2
x
−
1
)
(
3
x
2
+
1
)
Now, it's easy to find the roots of this polynomial in
C
that are:
α
=
1
/
2
,
β
=
i
/
3
and
γ
=
−
i
/
3
After calculating, we find that the answer is
2
.
Problem Loading...
Note Loading...
Set Loading...
Clever solution:
Note that 6 x 3 − 3 x 2 + 2 x − 1 = 6 ( x − α ) ( x − β ) ( x − γ )
Also, 1 + α + β + γ + α β + β γ + γ α + α β γ = ( α + 1 ) ( β + 1 ) ( γ + 1 )
Now plug in x = − 1 in our first equation to get that 6 ( − 1 − α ) ( − 1 − β ) ( − 1 − γ ) = 6 ( − 1 ) 3 − 3 ( − 1 ) 2 + 2 ( − 1 ) − 1 = − 1 2 or − ( 1 + α ) ( 1 + β ) ( 1 + γ ) = − 2
Thus, ( 1 + α ) ( 1 + β ) ( 1 + γ ) = 2